Using Coloured Cognitive Mapping to Support IS Development - Venable, John (Monash University, 2005)
This paper proposes and reports on research in progress on the development and evaluation of a new technique, Coloured Cognitive Maps (CCM), for use in problem formulation at the early stages of Information Systems Development. The paper develops a rationale for the need for proper problem analysis and formulation in IS Development and analyses the obstacles to doing it properly. The notation of coloured cognitive maps and a procedure to use them for problem analysis and solution derivation are described. The contributions of the CCM method in overcoming the identified problems with problem formulation are then analysed. Initial results in employing CCM by practitioners are briefly described.